Impact of physical frailty on the clinical outcomes of older patients hospitalized for pneumonia. Issue 10 (14th August 2021) - Yamada, Kanji; Iwata, Kentaro; Tachikawa, Ryo; Yoshimura, Yoshihiro; Kanejima, Yuji; Yamamoto, Akio; Ono, Kumiko; Honda, Akihiro; Kohara, Nobuo; Tomii, Keisuke; Ishikawa, Akira; Kitai, Takeshi
Abstract : Aim: This study aimed to assess the association between physical frailty and clinical outcomes among older patients hospitalized for pneumonia. Methods: This study examined 852 consecutive patients hospitalized for pneumonia between October 2018 and September 2020. Patients who were <65 years old, scheduled for admission, did not receive inpatient rehabilitation, or died during admission were excluded. A short physical performance battery (SPPB) test was performed by physical therapists upon discharge. The primary outcome measure was a composite endpoint of readmission or mortality due to any cause within 6 months of discharge. Results: In total, 521 patients (median age, 80 years; interquartile range, 74–86 years) were included in the analyses, and were divided into the following two groups: robust group with SPPB scores >9 ( n = 150), and physical frailty group with SPPB scores ≤9 ( n = 371). Of these, 346 (66.4%) patients were men; and the median SPPB score was 6 (interquartile range, 1–10). During the median follow‐up period of 53 days (interquartile range, 4–180 days), 92 (17.6%) patients were readmitted and 25 (4.8%) patients died. Patients with physical frailty were at an increased risk for the primary endpoint (hazard ratio, 2.21; 95% confidence interval, 1.44–3.41; P < 0.001); the risk remained significant after adjusting for multiple variables (adjusted hazard ratio, 1.70; 95% confidence interval, 1.05–2.74; P = 0.028). Conclusions: Among older patients with pneumonia, physical frailty status at discharge was an independent risk factor for readmission and mortality within 6 months after initial discharge. Geriatr Gerontol Int 2021; 21: 926–931 .